Penyidikan Tindak Pidana Pembunuhan Berencana Yang Secara Kolekti: Studi Kasus di Polres Bengkulu Tengah: Investigation of Premeditated Murder as a Collective Crime: A Case Study at the Central Bengkulu Police Station - Ela Darma Pertiwi; Alauddin; Rosmanila (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This article analyzes the investigation process of premeditated murder committed collectively within the jurisdiction of the Central Bengkulu Police Department. The study employs an empirical legal method with a socio-legal approach, relying on interviews with investigators, perpetrators, and victims’ families, as well as an examination of official documents. The findings reveal significant obstacles, including the perpetrators fleeing across regional boundaries, strong solidarity among the offenders, and the destruction of evidence. Investigators adopted cross-sectoral strategies and utilized forensic technology to overcome these challenges. This study emphasizes the importance of inter-agency coordination and an integrative approach in handling collective crimes.